Strategies for Prevention of Money Politics and Simultaneous Local Elections - Muslimah Muslimah; Rahmawati Rahmawati; M. Asad Imaduddin (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
Disclosure of Indonesia's campaign finance has been in the spotlight since the post-Suharto elections, with publications related to KPU campaign finance receipts, payments and reports. However, the applications revealed by campaign funds are never optimal. This article contributes to addressing two problems at once. First, conceptually money politics and in simultaneous local elections. This research is a normative legal research or doctrinal research which is explorative-analytic in nature. The data used is secondary data, in the form of primary legal materials and secondary legal materials. The findings show that the cause of money politics will still be influenced by cultural factors, poverty, education level, level of understanding of law, degree of understanding of religion, weak government institutions, weakness of oversight institutions and party apparatus as well as weak political cadres. Therefore, it is necessary to have effective participation and application of the Village model Anti-money politics in Pilkada. Maximization of social capital forms a village social movement that is anti-money politics.